Автор:
jovannyАвтор:
pennyАвтор:
jacksonАвтор:
xzavierАвтор:
emiliobadeАвтор:
davianАвтор:
bitsАвтор:
eanayhaАвтор:
giovannycrjaАвтор:
maciescobarПри x=1 выражение обращается в 0, значит (x-1) - множитель.
Выделяем:
x³+5x²+3x-9=x³-x²+6x²-6x+9x-9=x²(x-1)+6x(x-1)+9(x-1)=(x-1)(x²+6x+9)=(x-1)(x+3)²
Автор:
cristianshawДобавить свой ответ
Предмет:
Русский языкАвтор:
braelynОтветов:
Смотреть
Предмет:
ЛитератураАвтор:
emma68Ответов:
Смотреть
Предмет:
Русский языкАвтор:
sandrarl3cОтветов:
Смотреть
Предмет:
Қазақ тiлiАвтор:
sienna67Ответов:
Смотреть